Role of Acetylsalicylic Acid in Cytokine Stimulation of Macrophages in Antibody-Dependent Cellular Cytotoxicity (ADCC) - M. Jäpel; H. Lötzerich; K. Rogalla (Hindawi Limited, 1994)
In addition to the spectrum of biological action already known to be exhibited by acetylsalicylic acid (ASA) as an analgesic, anti-inflammatory and platelet aggregation inhibitor, there is growing evidence of a stimulatory effect on the immune system. ASA has been found to increase the production ofcytokines and to increase the activity of various leukocytes. The action of ASA on the activity of mouse peritoneal macrophages was therefore investigated in the present study. Therapeutically effective concentrations of ASA, which are known to decrease levels of prostaglandins, had neither a stimulating nor an inhibiting influence on antibody-dependent cellular cytotoxicity (ADCC) or on the binding capacity of macrophages with regard to SW 948 tumour cells. Likewise ASA had little or no adverse effect on the capacity of the macrophages for stimulation by interferon-gamma (IFN-gamma) and interleukin-4 (IL-4). Taken together, the immunostimulant effect of ASA shown in the literature as an increased production of interleukin-2 (IL-2) and IFN, could not be confirmed on the basis of the macrophage cytotoxiclty.